2018
DOI: 10.1007/s10803-018-3731-6
|View full text |Cite
|
Sign up to set email alerts
|

The Severe End of the Spectrum: Insights and Opportunities from the Autism Inpatient Collection (AIC)

Abstract: Research on individuals severely affected by autism, including those who are minimally verbal, have intellectual disability or challenging behaviors, has become less common. The Autism Inpatient Collection (AIC) was initiated so data on this group is available to the research community. Ten studies utilizing phenotypic data from the first 350 AIC participants are presented. Greater autism severity, sleep disturbance, and psychiatric disorders are risks for hospitalization; fluently verbal youth experience more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Thus, despite interest in the comorbid psychiatric conditions in people with ASD, there is a paucity of studies that focus on the segment of the population most severely affected, the ~30% of individuals with ASD who remain non- or minimally verbal beyond school-age (26, 27). In an effort to fill this gap, a research collaborative between several academic and medical institutions was established in 2014, with the goal of conducting common comprehensive assessments on children and adolescents with ASD admitted to inpatient psychiatry care units [the Autism Inpatient Collection; AIC; (28)]. A preliminary paper reporting on 147 participants showed that expressive language impairment (being non-, or minimally verbal) affected 52% of the sample, 43% had intellectual disability, and 27% engaged in self-injurious behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, despite interest in the comorbid psychiatric conditions in people with ASD, there is a paucity of studies that focus on the segment of the population most severely affected, the ~30% of individuals with ASD who remain non- or minimally verbal beyond school-age (26, 27). In an effort to fill this gap, a research collaborative between several academic and medical institutions was established in 2014, with the goal of conducting common comprehensive assessments on children and adolescents with ASD admitted to inpatient psychiatry care units [the Autism Inpatient Collection; AIC; (28)]. A preliminary paper reporting on 147 participants showed that expressive language impairment (being non-, or minimally verbal) affected 52% of the sample, 43% had intellectual disability, and 27% engaged in self-injurious behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In sum, the majority of previous studies did not enroll non- or minimally verbal youths with ASD and only more recent studies have focused specifically on this neglected “severe end of the spectrum” (26, 28). Expanding on this research, here we examined the type, frequency, and severity of psychiatric symptoms using the CASI-5 as our primary outcome measure, and the Emotion Dysregulation Inventory [ EDI ; (35)], a new measure designed to assess emotion control difficulties independently of IQ and verbal ability in individuals with ASD, in a group of MV children and adolescents with ASD who have never received inpatient psychiatric care.…”
Section: Introductionmentioning
confidence: 99%
“…Interviewing people with communication impairments is a relatively recent innovation, with scope for refinement (Siegel, 2018). The few researchers who have interviewed people with autism, have mainly focused on individuals who have expressive language and the ability to communicate independently (Kirby et al, 2015;Vine Foggo & Webster, 2017).…”
Section: Interview As a Data Collection Methods With People With Nonvementioning
confidence: 99%
“…Whilst there is a growing body of research pertaining to people with autism, a paucity of research concerning those with Level 3 (severe -nonverbal)(American Psychiatric Association [APA], 2013) autism is evident (Hills, Clapton, & Dorset, 2016). Communication and social barriers have prevented the inclusion of people with nonverbal autism as direct respondents in research opportunities to date (Siegel, 2018). This paper describes the methodological approach of a research study, Spirituality in the context of people with nonverbal autism.…”
Section: Introductionmentioning
confidence: 99%
“…Adults on the autism spectrum with co-occurring intellectual disability (ID) are critically underrepresented in the autism intervention literature (Siegel 2018). Adults with ID have only been included in approximately 6% of published studies (Russell et al 2019) yet are estimated to represent 30-40% of all individuals on the autism spectrum (Maenner 2020).…”
mentioning
confidence: 99%